PENGARUH KEAHLIAN TERHADAP PRESTASI KERJA YANG DIMEDIASI MOTIVASI KERJA PEGAWAI - Evodius Nasus; Patwayati Patwayati; Nasrul Nasrul (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2017)
This study aimed to examine and empirically analyze the effect of expertise on work achievement mediated by work motivation of staff at Benyamin Guluh Hospital in Kolaka regency. The study had an explanatory nature which aimed at explaining the position of variables under investigation as well as the relationship between them and the effect of one variable on the others.Results of the study showed that: (1) Expertise directly had a positively significant effect on work motivation. Changes in the expertise were positive and significant to the increase of work motivation; (2) Expertise directly had a positively significant effect on staff’s work achievement. The better the expertise, the higher the work achievement of staff at Benyamin Guluh Hospital in Kolaka regency; (3) Work motivation directly had a positively significant effect on staff’s work achievement. This fact indicated that high work motivation contributed to the increase of the work achievement of staff at Benyamin Guluh Hospital in Kolaka regency; (4) Expertise had an indirect effect on the work achievement of staff via work motivation. This meant that high expertise was be able to promote work motivation, and then affected the work achievement of staff at Benyamin Guluh Hospital in Kolaka regency.Keywords: Expertise, work motivation, staff’s work achievement